(untitled) (Oxford, 2006)
A complete exam preparation coursebook for secondary students workingtowards B1 and B2 level exams. Exam skills training through twelve topic-basedunits, with practice at two levels: B1 and B2. Suitable for classroom use orself-study.
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers,Examinations,Study guides,Giáo trình dành cho người nước ngoài,Bài thi,Hướng dẫn học